Comparative evaluation of the effects of different methods of post space preparation in primary anterior teeth on the fracture resistance of tooth restorations - Bahman Seraj; Sara Ghadimi; Ebrahim Najafpoor; Fatemeh Abdolalian; razieh khanmohammadi (Tabriz University of Medical Sciences, 2019)
Background. Severely damaged teeth do not have adequate structure to support the composite crown; therefore, use of the canal space has been suggested to increase retention. Furthermore, the effect of post space irrigation protocols on the fracture resistance of the primary anterior teeth has not definitely been studied in postoperative modalities. This study compared the fracture resistance of restorations of primary anterior teeth following irrigation of the post space with sodium hypochlorite and chlorhexidine with and without application of burs. Methods. Ninety-four extracted primary anterior teeth were selected. Root canal treatments were carried out, 4 mm of the post space was left empty and 1 mm was regarded as a bed. The post space was prepared with and without a bur and the irrigation procedures were carried out with 0.2% chlorhexidine and 2.5% sodium hypochlorite solutions. Composite posts were inserted into the canals and the crowns were restored. Following composite etching and light-curing, the fracture resistance of the restored teeth was determined by a universal testing machine. Results. In the sodium hypochlorite group, fracture resistance of the teeth was 376.8±107.29 N and 475.5±186.89 N without and with bur preparation, respectively. For chlorhexidine protocol, the values were 370.88±175.46 N and 430.85±178.22 N without and with bur preparation, respectively. The effect of irrigating material was not significant; however, the bur and irrigating preparation significantly increased the fracture resistance of the restored teeth (P=0.02). Conclusion. Post space irrigation with 0.2% chlorhexidine or 2.5% sodium hypochlorite did not significantly affect the fracture resistance of primary anterior teeth in the post treatment modality.